Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V; Perrini, G; Tomasello, M (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V.; Perrini, G.; Tomasello, M. (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563doi: 10.1080/10406630213563The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers